Nurses' Satisfaction Regarding the Use of Patient Handover Tools in the Patient Transfer Process to the Intensive Care Unit - Elçin Yıldırım; Serpil Topçu (Sağlık ve Hemşirelik Yönetimi Dergisi)
Aim: The study aimed to evaluate the effectiveness of using a patient handover tool during the process of patient transfer to the intensive care unit after surgery. Method: This descriptive and prospective study was conducted with 82 nurses who consented to participate following ethical committee approval and institutional authorization at Bursa City Hospital between July 15, 2023, and February 1, 2024, in the surgical intensive care units. Data collection tools, developed by the researcher and validated by experts, were employed. Results: It was determined that the items on the tool used in the patient handover process were largely completed. However, the documentation rate for isolation requirements (57.3%) and monitoring of the patient's drains (67.1%) was found to be relatively low. The participating nurses reported that 65.9% wished to continue using the tool in the intensive care unit, 96.3% found it helpful in understanding the patient's current condition, and 84.1% stated that it was beneficial in predicting potential complications. Significant differences were found between certain sociodemographic characteristics of the nurses and their satisfaction levels with the use of the handover tool. The average handover duration guided by the tool was found to be 115.48 seconds (≈1.92 minutes). Conclusion: Nurses indicated a preference for utilizing the patient handover tool during the handover process. Furthermore, significant associations were identified between satisfaction levels with the tool and the socio-demographic characteristics of the nurses.